MODEL DESAIN WEB SELF-PACED LEARNING UNTUK MICROLEARNING DENGAN PENDEKATAN HIGH-FIDELITY PROTOTYPING - Edi Kurniawan; Afdhal Syafnur; Zulkarnain Sirait; Willy Alfiandi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Digital transformation in education drives the need for flexible learning methods such as self-paced learning with microlearning. However, its effectiveness is highly influenced by the platform's design quality. This research aims to develop and evaluate a web design model supporting microlearning-based self-paced learning using a high-fidelity prototyping approach. The research method adopts the Design and Construct phase of Design-Based Research (DBR), which includes the implementation of a functional high-fidelity prototype and usability testing. Usability testing was conducted using two methods: the System Usability Scale (SUS) with 40 real users (37 Participants and 3 Admins), and Heuristic Evaluation (HE) by 7 expert evaluators. The SUS test results indicated an excellent level of usability with a combined average score of 82.5, categorized as "Excellent" (Grade B) and "Acceptable". The HE results identified 14 unique findings, comprising 4 "Major", 8 "Minor", and 2 "Cosmetic" issues, with primary problems related to H-1 (Visibility of System Status) and H-5 (Error Prevention). This study concludes that the proposed high-fidelity prototype design model is highly successful and well-received by users, while also yielding focused recommendations for improvement based on the 4 critical findings. Keywords: Self-Paced-Learning; Microlearning; Desain-Web; High-Fidelity-Prototype; Usability. Abstrak: Transformasi digital dalam pendidikan mendorong kebutuhan akan metode pembelajaran fleksibel seperti self-paced learning dengan microlearning. Namun, efektivitasnya sangat dipengaruhi oleh kualitas desain platform. Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi model desain web yang mendukung self-paced learning berbasis microlearning menggunakan pendekatan high-fidelity prototyping.   Metode penelitian mengadopsi Design and Construct dari Design-Based Research (DBR), yang mencakup implementasi high-fidelity prototype fungsional serta pengujian usability.   Pengujian usabilitymenggunakan dua metode: System Usability Scale (SUS) terhadap 40 pengguna nyata (37 Peserta dan 3 Admin), dan Heuristic Evaluation (HE) oleh 7 evaluator ahli. Hasil pengujian SUS menunjukkan tingkat kegunaan sangat baik dengan skor rata-rata gabungan 82.5, yang dikategorikan "Excellent" (Grade B) dan "Acceptable". Hasil HE mengidentifikasi 14 temuan unik, terdiri dari 4 "Mayor", 8 "Minor", dan 2 "Kosmetik", dengan masalah utama pada H-1 (Visibilitas Status Sistem) dan H-5 (Pencegahan Error). Penelitian ini menyimpulkan bahwa model desain high-fidelity prototype yang diusulkan sangat berhasil dan diterima baik oleh pengguna, serta menghasilkan rekomendasi perbaikan yang terfokus pada 4 temuan kritis. Kata kunci: Self-Paced-Learning; Microlearning; Desain-Web; High-Fidelity-Prototype; Usability.